Three-dimensional DEM-CFD analysis of air-flow-induced detachment of API particles from carrier particles in dry powder inhalers - Jiecheng Yang; Chuan-Yu Wu; Michael Adams (Elsevier, 2014)
Air flow and particle-particle/wall impacts are considered as two primary dispersion mechanisms for dry powder inhalers (DPIs). Hence, an understanding of these mechanisms is critical for the development of DPIs. In this study, a coupled DEM-CFD (discrete element method-computational fluid dynamics) is employed to investigate the influence of air flow on the dispersion performance of the carrier-based DPI formulations. A carrier-based agglomerate is initially formed and then dispersed in a uniformed air flow. It is found that air flow can drag API particles away from the carrier and those in the downstream air flow regions are prone to be dispersed. Furthermore, the influence of the air velocity and work of adhesion are also examined. It is shown that the dispersion number (i.e., the number of API particles detached from the carrier) increases with increasing air velocity, and decreases with increasing the work of adhesion, indicating that the DPI performance is controlled by the balance of the removal and adhesive forces. It is also shown that the cumulative Weibull distribution function can be used to describe the DPI performance, which is governed by the ratio of the fluid drag force to the pull-off force.